Improving Listening In IELTS Using Paraphrasing - Tiara Kristina Pasaribu; Donna Ria Pasaribu; Jubilezer Sihite; Bernas Alonso Lumban Gaol; Erika Cahaya Manurung (LPPM Universitas PGRI Sumatera Barat, 2024)
This research was limited to the Listening Section on IELTS, specifically Sections 3 and 4, which consisted of academic discourse on listening comprehension. The subjects of this research were the Semester 2 students in the Intermediate English Listening class, which consisted of 26 students. The problem of this research was to find out whether using the paraphrasing strategy could improve students' listening skills in the IELTS Listening Section. The aim of the research was to find out whether the paraphrasing strategy was able to improve students' listening skills in the IELTS Listening Section. Students were taught the strategies of paraphrasing in IELTS in which students were required to know the meaning of different words such as synonyms, antonyms, knowledge of grammatical changes in active and passive sentences, changing the type of words they heard, rephrasing the main idea of what they heard, and various other strategies. The research method was class action research that applied four phases, that is: planning, action, observation, and reflection. After two cycles, it can be concluded that there was a significant improvement at the end of the second cycle. The average at the end of the first cycle was 69, while at the end of the second cycle was 81. Qualitative data also supported the increase in the students' abilities in the IELTS Listening section. Students were enthusiastic, motivated, and interested in participating in the two cycles. The criteria of success have been achieved after cycle 2, as the percentage of improvement has reached 88% of students with scores of 75% and above. Therefore, the conclusion that can be drawn is that the paraphrasing strategies have been beneficial in helping students’ ability to improve their listening skills for the IELTS. Paraphrasing strategies consequently help sudents be motivated to increase their vocabulary level and their grammatical knowledge.